2016
DOI: 10.11648/j.cmr.20160503.17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia in Pregnancy Among Women Visiting Antenatal Clinic in Bingham University Teaching Hospital Jos, Nigeria

Abstract: In developing countries such as Nigeria, anaemia in pregnancy is thought to be one of the most common problem affecting pregnant women accounting for a significant level of maternal morbidity and mortality. This study was carried out to determine the prevalence of anaemia in pregnancy among women visiting Antenatal Clinic (ANC) in Bingham University Teaching Hospital (BHUTH). This is a cross sectional descriptive study conducted from August to September, 2015 on two hundred and thirty seven (237) women. A semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…The high prevalence of anemia in pregnancy among women of Hausa/Fulani and the absence of anemia among the other tribes in this study may be due to the fact that the study was conducted in a predominantly Hausa/Fulani LGA. Prevalence of anemia was higher among multiparous women (78.5%) compared to primiparous women, this is similar to the findings in a study in Jos where the prevalence of anemia among multiparous women was (61.2%) (Paul et al, 2016) suggesting that recurrent exposure to pregnancy reduces the iron store in the body. About half of the respondents 162(50.8%) booked for antenatal care in the third trimester, while few 23 (7.2%) of them booked in the first trimester, suggesting that women in the study area do not begin antenatal care early in pregnancy, this is similar to the findings in other studies conducted in Azare and Abeokuta where (2.5%) and…”
Section: Discussionsupporting
confidence: 88%
“…The high prevalence of anemia in pregnancy among women of Hausa/Fulani and the absence of anemia among the other tribes in this study may be due to the fact that the study was conducted in a predominantly Hausa/Fulani LGA. Prevalence of anemia was higher among multiparous women (78.5%) compared to primiparous women, this is similar to the findings in a study in Jos where the prevalence of anemia among multiparous women was (61.2%) (Paul et al, 2016) suggesting that recurrent exposure to pregnancy reduces the iron store in the body. About half of the respondents 162(50.8%) booked for antenatal care in the third trimester, while few 23 (7.2%) of them booked in the first trimester, suggesting that women in the study area do not begin antenatal care early in pregnancy, this is similar to the findings in other studies conducted in Azare and Abeokuta where (2.5%) and…”
Section: Discussionsupporting
confidence: 88%
“…The 46% prevalence of Anaemia reported in this study is slightly higher than the value of 40.4% reported by Dim and Onah 18 working in the same city earlier a decade ago but higher than the 56% reported in 2016 by Esike et al 10 working in nearby Abakaliki all in the same south east region of Nigeria. It is however slightly different from the rate of 35.3% reported by Anorlu et al 13 working in the south west region, 51.8% reported by Bukar et al 19 working in northern Nigerian, 43.5% reported by Bassi et al 20 working in the North Central and 31.8% by Olatunbosun et al 21 working in the South Region of the country. However, this is not comparable to the cross sectional survey conducted in four Nigerian States (Jigawa, Katsina, Yobe, Zamfara) where the prevalence rate of anaemia was estimated to be 61.2%-88.7%.…”
Section: Resultscontrasting
confidence: 60%
“…The 4.35% of severe Anaemia reported in the study also contradicts other recent studies from southeastern Nigeria 24,25 and Ibadan, Western Nigeria, 26 where no case of severe Anaemia was noted, unlike in Shagamu, Western Nigeria, 27 where 0.7% of the anemic pregnant women were severely anemic. This was also higher than the lower than 2.1% by Bukar et al 12 Reports from Bassi et al 20 working in Jos showed that 2% of pregnant women had severe anaemia, which are comparable with those from Bida, Niger state, Nigeria. [28][29][30] However, it can be noted that the level of sever anamic pregnant women (4.35%) could be an isolated case as reports from the south east especially from the same Enugu showed no presence of severe Anaemia as reported here.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In Zambia, the magnitude of antenatal depression is not well understood. One cross-sectional study conducted at The University Teaching Hospital reported a prevalence of 42% out of 206 pregnant women interviewed 12 . A qualitative study conducted in the different stages of the perinatal period reported the presence of mental distress in the four different domains: worry about HIV status and testing; uncertainty about survival from childbirth; lack of social support; and vulnerability/oppression and concluded that identifying mental distress and prompt referral for interventions is critical to improving the mental health of the mother and prevent the effects of mental distress on the baby 13 .…”
Section: Introductionmentioning
confidence: 99%